2017
DOI: 10.1158/1078-0432.ccr-16-1691
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preservative and Temperature on the Analysis of Circulating Tumor DNA

Abstract: Analysis of genomic alterations in cell-free DNA (cfDNA) is evolving as an approach to detect, monitor, and genotype malignancies. Methods to separate the liquid from the cellular fraction of whole blood for circulating tumor DNA (ctDNA) analyses have been largely unstudied, although these may be a critical consideration for assay performance. To evaluate the influence of blood processing on cfDNA and ctDNA quality and yield, we compared the cfDNA levels in serum with those in plasma. Given the limitations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 34 publications
7
115
1
Order By: Relevance
“…The tubes were handled and centrifuged within 14 days according to the manufacturer's instructions (double spin at 1,600 g and 16,000 g ). Previous research has shown that the cfDNA quantity from BTC and EDTA tubes was highly comparable, with cfDNA quantity from the BTC tubes remaining stable over time . cfDNA was isolated from 4 mL of plasma using the QIAamp Circulating Nucleic Acid Kit (Qiagen, Venlo, the Netherlands) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The tubes were handled and centrifuged within 14 days according to the manufacturer's instructions (double spin at 1,600 g and 16,000 g ). Previous research has shown that the cfDNA quantity from BTC and EDTA tubes was highly comparable, with cfDNA quantity from the BTC tubes remaining stable over time . cfDNA was isolated from 4 mL of plasma using the QIAamp Circulating Nucleic Acid Kit (Qiagen, Venlo, the Netherlands) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…For blood storage until analysis, the choice between commonly available EDTA tubes and cell stabilizing tubes should depend on the transportation time: for in‐house samples processed within 4–6 hours after collection, EDTA tubes are sufficient to extract cfDNA. 62–64 Longer periods of storage or transportation warrant the use of tubes containing cell‐stabilizing reagents . From these tubes, steady cfDNA quality can be obtained after up to 1 week of storage, independent of the temperatures tested in the analysis (4°C or room temperature) .…”
Section: Cfdna Extraction From Blood and Other Materialsmentioning
confidence: 99%
“…In a comparative study, cfDNA concentrations from identical artificially spiked plasma samples extracted at 56 different laboratories revealed wide variations in cfDNA yields ranging from 2.87 to 224.02 ng/mL with a median of 23.15 ng/mL of plasma . While it is still debated whether blood plasma or serum contains more and higher quality cfDNA, there is evidence that serum is prone to high‐molecular‐weight DNA contamination due to delayed processing . For cfDNA‐based analytics of primary and metastatic brain tumors it is important to note that cerebrospinal fluid harbors more ctDNA than blood as the blood‐brain barrier reduces molecular exchange with the peripheral circulation, total volume is comparably low and contamination by cellular DNA is limited .…”
Section: Cfdna Extraction From Blood and Other Materialsmentioning
confidence: 99%
“…Commercially available cfDNA BCT blood collection tubes are claimed to stabilize nucleated blood cells, preventing the release of cellular DNA into plasma, and also inhibiting degradation of cfDNA . Commercially available cfRNA BCT blood collection tubes are also claimed to stabilize nucleated blood cells, preventing the release of cellular DNA into plasma, and also inhibiting degradation of cfRNA …”
Section: Quality Control and Preanalytical Parameters In Liquid Biopsiesmentioning
confidence: 99%
“…The influence of preanalytical parameters on ctDNA and CTC analysis is crucial and could potentially explain the various discrepancies reported in the literature and the poor reproducibility and differences in handling procedures . Numerous studies have already evaluated parameters potentially affecting ctDNA concentration and fragmentation and have described the optimal preanalytical handling conditions for ctDNA analysis …”
Section: Quality Control and Preanalytical Parameters In Liquid Biopsiesmentioning
confidence: 99%